Stagecraft fundamentals : a guide and reference for theatrical production - Carver, Rita Kogler (Boston : Focal Press, 2009)
This book tackles every aspect of theatre production. The history of stagecraft, safety precautions, lighting, costumes, scenery, career planning tips, and more are discussed with modern, color examples that display both step-by-step procedures and the finished product.--[book cover]
Introduction -- pt. 1: History and art. Where we've been and where we're going: a brief history and introduction ; It's all about collaboration: design for theatre ; Making it visual: composition ; Black and white are colors TOO!: color theory ; Creating the stage picture: drawing, rendering, and drafting -- pt. 2: Safety and scenery. Safety first!: safety ; Setting it all up: scenic tools and materials ; How to get it done: scenery standard techniques and practices ; A little dab will do ya: paint -- pt. 3: Rigging and lighting. Hanging by a thread: rigging ; House to half ... lighting -- pt. 4: Costumes and makeup. All dressed up with someplace to go: costumes ; Put on a happy face: makeup -- pt. 5: Sound and special effects. Is this thing out?: sound ; The magic behind the curtain: special effects -- pt. 6: Stage management and careers. Warning, standby, GO!: stage management ; What's next?: career choices ; Still confused?: glossary and lots more!
Includes indexes.
Keywords: Theater -- Production and direction; Theater management